The Productivity Impact of Business Visits across Industries - Mariacristina Piva; Massimiliano Tani; Marco Vivarelli (Institute of Labor Economics (IZA), 2020)
This paper builds on and considerably extends Piva, Tani and Vivarelli (2018), confirming the key role of Business Visits as a productivity enhancing channel of technology transfer. Our analysis is based on a unique database on business visits sourced from the U.S. National Business Travel Association, merged with OECD and World Bank data and resulting in an unbalanced panel covering 33 sectors and 14 countries over the period 1998-2013 (3,574 longitudinal observations). We find evidence that BVs contribute to fostering labour productivity in a significant way. While this is consistent with what found by the previous (scant) empirical literature on the subject, we also find that short-term mobility exhibits decreasing returns, being more crucial in those sectors characterized by less mobility and by lower productivity performances.
Keywords: J61; J61; O33; 330; business visits; labour mobility; knowledge diffusion; R&D; productivity